Preventive and Predictive Maintenance in Telephone Exchanges: Theoretical Review - Muñoz Pinto, Dirxon Javier; Munoz Pinto, Dirwin Alfonzo (Athenea Engineering sciences journal, 2025)
This study presents a bibliographic review conducted in Latin America using the PRISMA methodology to analyze preventive and predictive maintenance strategies applied to hybrid telephone exchanges. An initial search in academic databases yielded 1,034 records, which were narrowed down to 17 studies through rigorous inclusion criteria. The findings emphasize that preventive maintenance, based on scheduled inspections, addresses deficiencies in advance, ensuring service continuity and enhancing system performance. Predictive maintenance, supported by real-time monitoring and data analysis, identifies anomalies and potential failures before they occur. This approach extends equipment lifespan and reduces the need for corrective interventions, which are typically costly and disruptive. It is concluded that these maintenance strategies are complementary and, when integrated, contribute to efficient operation, optimal planning of interventions, and the sustainable and cost-effective management of hybrid telephone exchange systems.